Communicative activities in the teaching of Arabic language in Malaysian secondary schools - Zailaini, M.A.; Dahan, H.B.A.M.; Ismail, W.M.; Hussin, Z.; Saad, R.M. (Sakarya University, 2015)
This is a case study which intends to look at communicative activities carried out by teacher of Arabic. The participant involved in this study are a teacher teaching Communication in Arabic and a class of Form Two students. The teacher was selected based on a number of criteria among which was knowledge regarding communicative activities and teaching experience of more than ten years. Data were collected through observation, interviews and documents within a period of four months. The results of the study revealed eleven features or criteria of communicative activities in the teaching of Arabic. These criteria for communicativeness were adapted from the communicative activity continuum used by Harmer (1983) and the principles of communicative activities by Johnson (1982). The criteria which were identified were that the activities should be those which stimulated a communicative desire and had a communicative purpose. The focus of the activities was on meaning or content which could be conveyed in a variety of structural forms. Intervention by the teacher and control by materials should be reduced. Effective communicative activities were those where there was information transfer, information gap, jigsaw activity and task dependency.